Digital Humanitarian Spaces In The Disaster Management Process: A Case Study of Indonesia - Chusnul Chotimah, Hidayat; Setyo Pratiwi, Tiffany (LPPM Universitas Lampung, 2022)
Advanced information and communication technology have triggered an evolution in human activities in response to the threat of a disaster. Through appropriate disaster management, damage and loss can be anticipated. The research employed a qualitative descriptive technique to analyze humanitarian actors' roles in responding to the threat of natural or non-natural disasters by integrating technology. The information was gathered through library research and in-depth interviews with various stakeholders involved in disaster management in Indonesia. The results showed that innovation-based disaster management for three stages (pre, during, and post-disaster) has opened Indonesia's humanitarian spaces. First, the pre-disaster phase includes mitigation and preparedness. It emphasizes several elements, including preparedness data, citizen reporting, crisis mapping, the Internet of Things, Artificial Intelligence, and data visualization through video, virtual reality, and innovative financing. Second, during a disaster, the response focuses on utilizing humanitarian ID, biometrics, 3D printing, drones, cash transfer programming, monitoring, and evaluation. Third, post-disaster efforts include area reconstruction and risk reduction through the use of smart city and educational technologies.